Legal basis for the work of credit information and rating companies( A comparative study ) - Abdul Hissein Salim, Researcher. Habiab; Abdul Baqi Yousif , Prof. Asst. E'tedal (Basra studies journal, 2025)
There are many methods for collecting information and analyzing the financial situation of customers, either by banking inquiry or classification systems on the one hand, and specialized companies on the other hand. All of them agreed in their goal, which is to reach the true financial position of customers, for the purpose of maintaining the stability of the economic situation in the market and granting credit. Therefore, bank credit is the goal of the activity of these entities for those who deal with them. As for the company, the credit evaluation is its goal or objective in preparation for its classification, which is the basis of its work and its commercial activity is based on it.